Diplomacy theory and practice - Berridge, Geoff (Palgrave Macmillan, 2010)
"Diplomacy, widely recognized as the standard textbook on its subject and already translated into six languages, has been comprehensively updated, reorganized and greatly expanded. There are new chapters on consuls, public diplomacy, special envoys, and how agreements are best followed up, the last featuring a close look at no torture agreements"--Provided by publisher.